Meningkatkan Kemampuan Bekerja Sama Melalui Fun Games Di Balai Perlindungan Dan Rehabilitasi Sosial Remaja (BPRSR) - Nafisa Kirani Azzahra; Nilam Meinanda Zakyati; Titik Febianti; Bunga Ayu Prabowo Putri; Jilan Rizqi Azizah (CV. ITTC INDONESIA, 2024)
The ability to work collaboratively is a crucial skill that enhances team effectiveness and success in both social and professional environments. At the Center for Protection and Social Rehabilitation for Youth (BPRSR), improving teamwork skills is a primary focus in supporting rehabilitation and skill development among adolescents. This article examines the implementation of fun games as an intervention method to enhance teamwork skills among adolescents undergoing social rehabilitation. Fun games are designed to create an enjoyable atmosphere, strengthen communication, build trust, and foster collaboration among participants. Two types of fun games were utilized in this study: sarong relay and jumping suit. This research employed a qualitative approach, involving direct observation. The results indicate that fun games significantly improve teamwork skills, as evidenced by increased engagement, group problem-solving abilities, and the quality of social interactions. The article concludes that fun games are an effective method that can be integrated into social rehabilitation programs for adolescents.